CRENÇAS DOCENTES SOBRE ENSINO REMOTO NO CONTEXTO DA RESIDÊNCIA PEDAGÓGICA DA UFN - Leão, Mirca Mendes (2024)
This master's thesis aims to analyze teachers' beliefs regarding remote teaching during the COVID-19 pandemic, using as corpus the texts produced for a report book on the experiences of the Pedagogical Residency program at UFN, published by Editora Fi. The research is based on the application of the evaluativity system, a theoretical methodological approach developed by Martin and White (2005), to map and classify the linguistic indices that denote teachers' attitudes, distinguishing between affect, judgment, and appreciation. Additionally, it seeks to reclassify these indices into emerging belief categories, culminating in the discussion of the perceptions revealed by the data. The adopted methodology consists of qualitative analysis of the texts produced by teachers participating in the Pedagogical Residency program, focusing on the identification and classification of linguistic indices expressing affect, judgment, and appreciation. These indices are then grouped into categories of emerging beliefs, which are analyzed and discussed in relation to the research objectives. The results of the research reveal a diversity of beliefs among teachers regarding remote teaching during the pandemic, ranging from feelings of frustration and overload to recognition of the learning and professional development opportunities provided by this challenging context. The analysis of teachers' beliefs contributes to a deeper understanding of the challenges faced and the strategies adopted in the context of remote teaching. The relevance of this research lies in its contribution to reflecting on initial and continuing teacher education, especially in the context of remote teaching. Understanding educators' beliefs is crucial for improving educational systems locally and globally. Moreover, the study fits within the field of languages, providing an in depth view of the role of language in all aspects of human life, which is fundamental for Applied Linguistics. Finally, this dissertation contributes to enhancing teaching practice and the development of educational systems in a context of remote teaching during the pandemic. By understanding teachers' beliefs and their implications for pedagogical practice, it is hoped to promote a more inclusive, equitable, and effective education for all students.